Ensuring the Performance of Small and Medium-Sized Enterprises (Journal of Universal Excellence, 2026)
Research Question (RQ): The research question I asked is: Is the use of the EFQM model in small and medium-sized companies important for successful operation and what does it contribute to?Purpose: The purpose of the assignment is to acquire a lot of different foreign and Slovenian professional literature and compare it with each other. The aim of the assignment is to find out whether the EFQM model is also used in small and medium-sized companies and what the use of only this helps.Method: The method I used is aimed at a systematic review of references. It is a research method that represents the identification, evaluation and interpretation of all available research that answers the research questions posed in a specific field.Results: We found that the use of the EFQM model in small and medium-sized companies is important, because only this helps to make business easier and better.Organization: The research would help the organization, as it would obtain information and additional suggestions regarding the use of the EFQM 2020 model. More and more organizations would decide to implement the EFQM model in the company, due to the good results that this model brings.Society: For organizations that would start using the EFQM model, society would also change. We would start working in a team, listening to each other, and accepting criticism and new suggestions.Originality: Small and medium-sized companies realize that it is better for the company if they operate according to the EFQM model.Limitations/Future Research: The research was done with the help of various references. There are still many possibilities to explore.
Keywords: EFQM model; small companies; medium-sized companies; quality; work performance; company performance; RADAR matrices; employees